The Theory and Practice of Integrating Invertible Counterpoint into Classical Theme-Types - Franck, Peter (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2012)
This essay investigates the use of invertible counterpoint within conventional theme-types encountered within Classical-style works. Whereas recent research has focused on how this contrapuntal technique provides a means of creating continuity, this article expands the purview by elucidating how it works in concert with theme-types, forms regulated by cadences (devices that arguably suppress continuity). A basic model provides the theoretical framework with which to analyze excerpts from a selection of works by Beethoven, Haydn, and Mozart. The analyses reveal that some theme-types are more successful than others at integrating invertible counterpoint into their formal design. Moreover, the analyses uncover the purpose of using invertible counterpoint within theme-types.